Analisis Faktor-faktor yang Mempengaruhi Proses Rekrutmen dan Seleksi - Ninawati Ninawati; Fransiska Liska; Veronika Tiara; Yusawinur Barella (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Effective Human Resources (HR) management is the key to the success of every company in achieving its strategic goals. In this context, recruitment, selection and placement of employees plays an important role as the first process that determines the quality and performance of a company's workforce. This study covers recruitment, selection, factors influencing selection, as well as the recruitment and selection process. The data collected is analyzed comprehensively to identify patterns, trends, and relationships between the recruitment and selection process, its factors, and placement in organizational performance. The results of this study are intended to provide valuable insights for human resource managers. The practical implications of this research will lead to the development of selection factors, more accurate recruitment and selection processes, and more targeted staff placement, which will ultimately improve overall organizational performance.